2018
DOI: 10.18203/2349-3291.ijcp20181545
|View full text |Cite
|
Sign up to set email alerts
|

Study of thyroid profile in malnourished children (6 months - 5 years) admitted in the nutritional rehabilitation centre and paediatric ward NSCB Medical College Jabalpur, India

Abstract: Background: Globally, PEM continues to be a major health problem in developing countries and the most important risk factor for illnesses and death especially among young children. The research was conducted to study the effect of thyroid profile in malnourished children (6 month-5 years) admitted in tertiary care center in Central India.Methods: A cross sectional hospital based observational study was carried out in tertiary care hospital NSCB MCH Jabalpur. 80 malnourished children were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…7 The previous study showed that malnutrition affected the thyroid function in children as malnutrition children have lower thyroid serum levels. 12 Malnutrition is one of the main manifestations of TB, which may explain the abnormalities of thyroid function in TB. In malnutrition, as an adaptive response, the thyroid structure changes, which causes disturbance in thyroid gland function, resulting in reduced thyroid hormone in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…7 The previous study showed that malnutrition affected the thyroid function in children as malnutrition children have lower thyroid serum levels. 12 Malnutrition is one of the main manifestations of TB, which may explain the abnormalities of thyroid function in TB. In malnutrition, as an adaptive response, the thyroid structure changes, which causes disturbance in thyroid gland function, resulting in reduced thyroid hormone in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results was comparable with the study conducted by Lazarus M et al, which report the mean value of T3, T4 and TSH were 99.3ng/dl, 6.0ug/dl and 2.0 mIU/I respectively. 13 We estimate that majority of patients (47.…”
Section: Operational Definitionsmentioning
confidence: 99%